PENGEMBANGAN BAHAN AJAR MEKANIKA TANAH BERBASIS E-MODUL PADA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN, UNIVERSITAS NEGERI JAKARTA - ANNA ELVARITA (Jurnal Pensil : Pendidikan Teknik Sipil, 2020)
The research aim to develop teaching materials for electronic module of soilmechanicssubject.ResearcherusingResearchandDevelopment(R&D)using Borg and Gall model which has been simplified by Sugiyono. This research conducted the steps of research and development: (1) Research and information collecting, (2) Planning, (3) Develop preliminary form of product, (4) Preliminary field testing, (5) Main product revision, (6) Main field testing, (7) Operation product revision, (8) Operational field testing, (9) Final product revision and (10) Dissemination and implementation. This research uses non-test instruments data collection techniques, namely questionnaires. Questionnaires were given to material experts and media experts to test the feasibility of teaching material for electronic module of soilmechanics. The results of the feasibility of teaching material for electronic module of soil mechanics subject is consists of 16 learning activities are as follows: a) Assessment by media experts gets 90,835% which is categorized as very good; b) Assessment by material experts gets 80,69% which is categorized as good. Based on the results of feasibility, can be concluded that of teaching material for electronic module of soil mechanics is appropriate and suitable for use as a variation for learning on soil mechanics subject by lecturer and students. Keywords: Teaching material, e-module, soil mechanics